Time and History in the Memories of Soviet Generations - Vinogradnaitė, Inga (Baltic Journal of Political Science, 2018)
This article aims to reconsider how and where the boundaries within Soviet generations as differentiable memory communities could be established. On the basis of Mannheimian theory of generational units and the theory of narration, as based on the conceptual metaphors of container, a method to identify the boundaries between generations was devised. The method was applied to biographical narratives, collected during the summer of 2017, and revealed the existence of different history-related calendars to structure time in the biographical past.